2014
DOI: 10.1089/met.2013.0120
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Gene Polymorphism in Patients with Nonalcoholic Fatty Liver Disease in Comparison to Healthy Controls

Abstract: As the first-time-in-humans controlled study related to investigation of TLR4 gene polymorphism in NAFLD, our findings contribute to the available data that TLR-4 signaling is pivotal for the pathogenesis of NASH and indicate that the TLR4 codon 299 heterozygous gene mutation (Asp299Gly) in humans may have a preventive role against the genesis of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 35 publications
0
24
0
4
Order By: Relevance
“…TLR4 gene polymorphism rs10759932 is found to be associated with lifetime cigarette smoking in bipolar disorder [414]. TLR4 codon 299 heterozygous gene mutation (Asp299Gly) is shown to be protective against nonalcoholic fatty liver disease (NAFLD) in humans [415].…”
Section: Tlr Polymorphism In Humans and Their Disease Associationmentioning
confidence: 99%
“…TLR4 gene polymorphism rs10759932 is found to be associated with lifetime cigarette smoking in bipolar disorder [414]. TLR4 codon 299 heterozygous gene mutation (Asp299Gly) is shown to be protective against nonalcoholic fatty liver disease (NAFLD) in humans [415].…”
Section: Tlr Polymorphism In Humans and Their Disease Associationmentioning
confidence: 99%
“…Hepatic TLR4 expression was further proved to be up-regulated in a large cohort of NASH patients when compared with NAFL patients, and this seems to occur in a setting of increased plasma endotoxin and fatty acids [135]. An importance of TLR4 signaling was further suggested by the study reporting that TLR4 codon 299 heterozygous gene mutation (Asp299Gly) was significantly lower in the NAFLD than in the control subjects [136].…”
Section: Intestinal Permeability Endotoxemia and Bacterial Translocamentioning
confidence: 95%
“…Our results are in accordance with a study by Day et al[13], in which biopsy-proven patients with NAFLD were genotyped for Asp299Gly single nucleotide polymorphism (SNP) in the TLR4 gene and no association was found between the susceptibility of NASH and the Asp299Gly TLR4 SNP. A recent study by Kiziltas et al[41] demonstrated that subjects with a heterozygous mutation in genotype 299 (Asp299Gly) were significantly lower in the NAFLD group than in the control group. The authors concluded that this mutation may have had a protective role against the genesis of NAFLD.…”
Section: Discussionmentioning
confidence: 99%